2004
DOI: 10.3748/wjg.v10.i18.2628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mifepristone on proliferation of human gastric adenocarcinoma cell line SGC-7 901in vitro

Abstract: Mifepristone effectively inhibited the proliferation of PR-positive human gastric adenocarcinoma cell line SGC-7901 in vitro through multiple mechanisms, and may be a beneficial agent against human adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…The remarkable inhibition of DNA synthesis induced by mifepristone was consistent with the abrupt interruption in cell growth observed within 24 h of exposure to the drug, the reduction in the number of cells in S phase, and the accumulation of cells in G 1 phase. Blockage of the cell cycle in G 1 after exposure to mifepristone has also been reported in human gastric adenocarcinoma cells (26), T-47D breast cancer cells (36), and in OVCAR-3 and A2780 ovarian cancer cells (27). In T-47D breast cancer cells, the inhibition of cell cycle progression by mifepristone was accompanied by induction of the cdk inhibitor p21 cip1 (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable inhibition of DNA synthesis induced by mifepristone was consistent with the abrupt interruption in cell growth observed within 24 h of exposure to the drug, the reduction in the number of cells in S phase, and the accumulation of cells in G 1 phase. Blockage of the cell cycle in G 1 after exposure to mifepristone has also been reported in human gastric adenocarcinoma cells (26), T-47D breast cancer cells (36), and in OVCAR-3 and A2780 ovarian cancer cells (27). In T-47D breast cancer cells, the inhibition of cell cycle progression by mifepristone was accompanied by induction of the cdk inhibitor p21 cip1 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent study using p53/BRCA1 -deficient mice, mifepristone prevented the formation of breast tumors (20), indicating its efficacy in not only impairing growth of established mammary tumors but also in inhibiting mammary tumorigenesis. Apart from breast cancer cells, mifepristone was reported to inhibit proliferation of normal and malignant endometrial cells (21 -24), prostate cancer cells (25), and gastric adenocarcinoma cell lines (26).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that mifepristone effectively inhibit the proliferation of certain types of hormone-dependent cancers such as progesterone receptor (PR)-positive breast cancer (14,15), ovarian cancer (16,17), endometrial cancer (18), prostate cancer (19), and gastric cancer (20). However, cervical carcinoma is a type of cancer that does not respond to hormonal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the cells repopulating the culture after being exposed to 3 rounds of CDDP treatment in our model system grow at the same pace as cells never exposed to CDDP, indicating that the cells do not seem to be genetically damaged by previous CDDP treatment. MF has been known for displaying anti-growth properties in different human cell types (15)(16)(17)(19)(20)(21)(22). We recently began to elucidate the molecular mechanisms involved in this effect on ovarian cancer cell growth (23).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, apart from this known contraceptive effect, MF has been reported to be effective as an anti-growth agent in endometriosis (15), leiomyomata (16), and breast (17,18), endometrial (19), prostate (20), gastric (21), and ovarian cancer cells (22). Our laboratory recently studied the molecular mechanisms of growth inhibition induced by MF in ovarian cancer cells and further defined its efficacy in an in vivo preclinical setting (23).…”
Section: Introductionmentioning
confidence: 99%